Produtos apícolas como antioxidantes em peixes frente a desafios oxidantes provocados por tebuconazole - Ferreira, Daiane (2013)
This paper present alternatives to mitigate the deleterious effects caused by pesticides from crops that contaminate ponds and water bodies, located very close to the growing areas. This proximity causes oxidative damage in fish. The suggested alternative is the use of bee products, which generate lower amounts of waste in the environment and has low cost. Since this organization has been growing crops only. We tested three different concentrations of honey (0,025g L-1; 0,075g L-1; 0,125g L-1), bee pollen (0,01g L-1; 0,03g L-1; 0,05g L-1), royal jelly (0,005g L-1; 0,015g L-1; 0,025g L-1) and propolis (0,01g L-1; 0,05g L-1; 0,1g L-1) and associated or not with fungicide tebuconazol (0,088mg L-1), apiculture products showed protective effect on fish, mainly inhibit / reverse lipid peroxidation, protein carbonylation and increase the activity of catalase, superoxide dismutase and glutathione S-transferase, contributing to the redox state of the cell. Our data suggest the antioxidant potential of honey, bee pollen, propolis and royal jelly added to water as protective substances against oxidative stress caused by agrochemicals, especially tebuconazole.